(untitled) (Palíndromo, 2018)
This article proposes a queer analysis of the artistic productions of Cindy Sherman and Yasumasa Morimura with the intent of question the lack of existence of a single and original individual in the contemporary society. The queer perspective allows to deconstruct a fix identity concept, providing a plural inter-pretation of art. Sherman and Morimura present themselves as changeable individuals with ephemeral identities in order to unstable the conventional gender identification system. Their productions are based on the process of an ever changing identity, to (de)construct themselves constantly. Throughout Sherman productions, the self-portrait language is analysed, questioning in what way can the self-portrait expose an individual in contemporary art. The individual is discussed in Morimura’s work through the camp aesthetics, combined with the concepts of exaggeration and imitation, questioning the permanency of an identity and the natural processes in the construction of an individual.